“The Riddle of Play.” On Cognitive Difficulties in the Theoretical Approach of Play - Grad, Jan (Sensus Historiae, 2024)
The “riddle of play” is determined by the research difficulties in its adequate scientific-cognitive approach. In the search for an answer to the question “what is play” and “why do people play?” the attention of researchers was directed to the origins, sources, vital functions, socio-cultural role and significance of ludic activity. However, the research to date “has shown the theoretical complexity of the phenomenon” and the substantive divergence of concepts, resulting from the cognitive questions posed and different theoretical and methodological assumptions. Thus, these concepts have not become the basis for constructing an overall adequate theory of play or its “true concept.” This circumstance has led many researchers to conclude that play cannot be scientifically defined. It is difficult to do so by focusing on the properties of play as a biologically determined activity of animals and humans on the one hand and, at the same time, capturing in one theoretical discourse the psychological aspects of participation in play as criteria for the cultural phenomenon of play on the other. This is the main cognitive source of the scientific “riddle of play.”